Сын: повести и рассказы / В. Ф. Сапаев - Сапаев Василий Федорович (Марийское книжное издательство, 2008)
Экземпляры: ф.18 (ретро) / Инвентарный номер: 45368 / Цена: / Авт.знак: С 19 / ББК: 84(2Рос=Мари)